A five year financial plan of the Caramel Pearl, Inc - Lorenzo, Loise Anne S., Eustaquio, Kamille Joy Z., Colastre, Monalyzza T., Aparicio, Maricel B., Alac, Anthony Mark E. , Gasatan, Faye Krishna S., Ribano, Shaira Marie G., Rodriguez, Rina Joyce R., Sesuca, Leilanie A.,. (Manila: PLM, 2017)
ABSTRACT Caramel Pearl Inc. has been in the manufacturing industry for more than four decades. It was established on year 1972 when they first introduced to Rustan's store their first product which is the caramel popcorn. Year 2014m Goldilocks Bakeshop Inc. acquired the entity and by then it was known for manufacturing and distributing their classic caramel popcorn and polvoron. Aside from Goldilocks, Caramel Pearl Inc. also supplies dairy products to Jaecas Specialty Food Products, Richbake, All Fresh and Clarmil Manufacturing. After the analyzing the entity's five year Financial Statement (2011-2015), the proponents found out that the entity is not able to manage its receivables efficiently which affects its profitability thus making it as the company's main problem. Hence, the proponents recommend for the entity to have an alternative course of action that involves the adaptation of reverse factoring. This is based on the justifications of when after the successful collection of payment from the account debtors; the factor subsequently remits the balance of the invoice amounts, usually called the reserve to the client, minus the factor's earned fees, and furnishes a buffer against defaults by clients and/or account debtors. This will allow the entity to transfer their credit risk and allow firms to borrow greater amount at lower costs. Its also only requires the legal environment to sell or assign accounts receivables bu does not require good collateral laws or efficient judicial systems. This action is expected to increase accounts receivable turnover and sales and decrease the administration costs and average collection period.
EXECUTIVE SUMMARY: D.M. Weceslao & Associates, Incorporated (DMWAI) was established on April 7, 1065. It vwas founded by Engr. Delfin M. Wenceslao with the main purpose of offering a wide range of construction related services that involve site and land development, land reclamation and real estate development. DMWAI has a present net worth of Php2,907,000.00 and is a large-scale corporation with 156 permanent employees/ Total Assets of Php29,050,602,055 and Working Capital amounting to Php2,907,026,510. This research aims to provide solutions in improving the entity$1 (Bs deficient collection of contracts receivables through enhancing the entity$1 (Bs credit policy, aiding the entity$1 (Bs difficulty in completing a project, improving the entity$1 (Bs credit and collection policy, increasing the cash and cash equivalents by 40% in the next 5 years and to complete projects on time. The company find it difficult to aid their inefficient collection of contracts receivables and completion of their projects on time. This leads the entity to rely on debt financing for their day to day operating expenses. Their financial ratios generally indicate that they are having problems with their unstable liquidity ratios. They have inadequate cash on hand that further shows their liquidity and efficiency problems. They also have an increasing number of receivables and it takes too long to be collected thus resulting to insufficient funds. Their lack of having current assets results to delay in the completion of their projects. After evaluating and anbalyzing the alternative courses of action based on the criteria and objectives, the researchers propose imposing an Interim Certificate to Construction Contracts to help with their difficulties in collection of the growing amount of contracts receivable. The company is allowed to issue an interim certificate indicating a milestone reached with the construction of a project. Along with this certificate, a partial invoice indicating partial payment based on the terms between the client and the company. Each time a milestone is reached during the construction, a partial payment shall be made by the client to the company. Implementation of this course of action makes collection of the receivable easier and faster. It also allows the company to use the partial payments as additional funds to use during the construction of a project which prevents the accumulation of delinquent payments after the completion of a project, pay their obligations on due, enhance the entity$1 (Bs credit and collection policy and provides additional cash therefore meeting the criteria set by the researchers.s
F
Keywords: academic writing